Budgeting In Production Company - Karolina RYBICKA (Communications of International Proceedings, 2022)
The management principles became the basis for the development of standard costing. Standard costs are usually associated with a manufacturing company's costs of direct material, direct labor, and manufacturing overhead. Rather than assigning the actual costs of direct material, direct labor, and manufacturing overhead to a product, many manufacturers assign the expected or standard cost. This means that a manufacturer's inventories and cost of goods sold will begin with amounts reflecting the standard costs, not the actual costs, of a product. Manufacturers, of course, still must pay the actual costs. As a result, there are almost always differences between the actual costs and the standard costs, and those differences are known as variances. The aim of the paper is to present – based on literature studies – definitions and issues connected with cost budgeting. There are used in the work following research methods: literature research as well as case study in production automotive company.
Keywords: planning process; budgeting; master budget; standard costing.